Medical updates 2023 - Abdullah, Aimy (Faculty of Medicine, 2023)
In line with our dedication to providing competent patient care and disseminating up-to-date knowledge to healthcare providers, the Medical Department of the Faculty of Medicine and Hospital Al-Sultan Abdullah duly organised the first UiTM Medical Updates conference on 21st of July and the 22nd July, 2023. Showcasing a lineup of distinguished speakers from our very own department, the conference highlighted clinically relevant updates on topics spanning all the diverse medical subspecialties available in Hospital Al-Sultan Abdullah.